Engaged Scholarship in the Context of Housing Insecurity and the Built Environment - Bradford, Lori; Kirychuk, Shelly; Martin, Wanda; McPhedran, Kerry (Engaged Scholar Journal, 2024)
In this issue, Wanda Martin, Kerry McPhedran, Shelley Kirychuk, and Lori Bradford, ESJ’s editor-in-chief, explores the concept of engaged scholarship within the realm of housing insecurity and the built environment. They shared their insights and experiences regarding the challenges and opportunities inherent in engaged scholarship, particularly in addressing inequities in housing and the built environment.